Role of myeloid-derived suppressor cells in the formation of pre-metastatic niche - Ya, Guoqi; Ren, Weihong; Qin, Rui; He, Jiao; Zhao, Shuo (Frontiers in Oncology, 2022)
Metastasis is a complex process, which depends on the interaction between tumor cells and host organs. Driven by the primary tumor, the host organ will establish an environment suitable for the growth of tumor cells before their arrival, which is called the pre-metastasis niche. The formation of pre-metastasis niche requires the participation of a variety of cells, in which myeloid-derived suppressor cells play a very important role. They reach the host organ before the tumor cells, and promote the establishment of the pre-metastasis niche by influencing immunosuppression, vascular leakage, extracellular matrix remodeling, angiogenesis and so on. In this article, we introduced the formation of the pre-metastasis niche and discussed the important role of myeloid-derived suppressor cells. In addition, this paper also emphasized the targeting of myeloid-derived suppressor cells as a therapeutic strategy to inhibit the formation of pre-metastasis niche, which provided a research idea for curbing tumor metastasis.